Drums, girls & dangerous pie - Sonnenblick, Jordan (Ketchum, Idaho : DayBue Insights, 2006)
The life of eighth-grader Steven Alper, already complicated by his friendship with two girls and a prodigious talent for drumming, is turned upside down when his five-year-old brother Jeffrey is diagnosed with leukemia.
G8
Keywords: Brothers -- Fiction; Leukemia -- Fiction; Friendship -- Fiction; Family life -- Fiction; Drum -- Fiction; Middle schools -- Fiction; Schools -- Fiction